2008
DOI: 10.1128/aem.01496-07
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of Histamine-Producing Bacteria in the Enological Environment and Instability of the Histidine Decarboxylase Production Phenotype

Abstract: Lactic acid bacteria contribute to wine transformation during malolactic fermentation. They generally improve the sensorial properties of wine, but some strains produce histamine, a toxic substance that causes health issues. Histamine-producing strains belong to species of the genera Oenococcus, Lactobacillus, and Pediococcus. All carry an hdcA gene coding for a histidine decarboxylase that converts histidine into histamine. For this study, a method based on quantitative PCR and targeting hdcA was developed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 32 publications
3
63
0
6
Order By: Relevance
“…For example, a multiplex PCR method for the simultaneous detection of LAB with the potential to produce histamine-, tyramine and putrescine-has been described (Marcobal et al, 2005). Furthermore, a quantitative real-time PCR for histamine-producing LAB (Fernández et al, 2006;Lucas et al, 2008) and for tyramine-producing bacteria has also been successfully applied to different stages of cheese manufacture including the final product (Ladero et al, 2008;Ladero et al, 2010b;Gardini et al, 2008). Molecular methods have also been designed to study histidine-and tyrosine-decarboxylase gene expression under conditions relevant for food fermentation (Rossi et al, 2011), including cheese making and sausage fermentation , respectively.…”
Section: Detection Of Amino Acid Decarboxylase-positive Microorganismsmentioning
confidence: 99%
“…For example, a multiplex PCR method for the simultaneous detection of LAB with the potential to produce histamine-, tyramine and putrescine-has been described (Marcobal et al, 2005). Furthermore, a quantitative real-time PCR for histamine-producing LAB (Fernández et al, 2006;Lucas et al, 2008) and for tyramine-producing bacteria has also been successfully applied to different stages of cheese manufacture including the final product (Ladero et al, 2008;Ladero et al, 2010b;Gardini et al, 2008). Molecular methods have also been designed to study histidine-and tyrosine-decarboxylase gene expression under conditions relevant for food fermentation (Rossi et al, 2011), including cheese making and sausage fermentation , respectively.…”
Section: Detection Of Amino Acid Decarboxylase-positive Microorganismsmentioning
confidence: 99%
“…A multiplex PCR method for the simultaneous detection of histamine-, tyramine-and putrescine-producing LAB has recently been proposed in order to identify BA-producing strains in wine and cider (Marcobal et al, 2005). In addition to end-point PCR analysis, a realtime quantitative PCR has been developed for detecting histamine-producing LAB in cheese and wine (Fernández et al, 2006;Lucas et al, 2008) or successfully used in the different steps of cheese manufacture and wine fermentation (Ladero et al, 2008;Nannelli et al, 2008).…”
Section: Detection Of Bas In Fermented Foodmentioning
confidence: 99%
“…MorenoArribas et al (2000) identified O. oeni as the main LAB responsible for histamine formation and lactobacilli for tyramine formation. Lucas et al (2008) identified 54 colonies of histamine producing isolates as O. oeni and despite the fact that histamine producing O. oeni are frequently found in wine, it was also found that LAB may lose this ability due to instability of the phenotype. Histamine producing LAB all carry an hdcA gene coding for a histidine decarboxylase (HDC) that converts histidine to histamine.…”
Section: Biogenic Aminesmentioning
confidence: 99%